2021
DOI: 10.1186/s13568-021-01299-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic acids on growth performance, intestinal morphology, and immunity of broiler chickens with and without coccidial challenge

Abstract: A total of 360-day-old broiler chicks were allocated into six groups in 2 (Coccidial challenge or not) × 3 (dietary treatments) factorial design. Three dietary treatments including: basic diet, basic diet plus organic acids (OAs) in drinking water, and basic diet plus OAs in the feed with and without coccidial challenge. The OAs in water or feed improved (P < 0.01) average body weight (ABW), average body weight gain (ABWG), and feed conversion ratio (FCR) as compared with the control diet during starter, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 78 publications
2
10
0
1
Order By: Relevance
“…Organic acids were demonstrated to improve the health of young broilers by enhance the immune system ( Dittoe et al, 2018 ). Broiler chicks fed with dietary organic acids showed higher serum IgG concentration ( Mustafa et al, 2021 ). Contrastingly, here we observed a decline in serum IgA and IgG contents of laying ducks fed diet with organic acid mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Organic acids were demonstrated to improve the health of young broilers by enhance the immune system ( Dittoe et al, 2018 ). Broiler chicks fed with dietary organic acids showed higher serum IgG concentration ( Mustafa et al, 2021 ). Contrastingly, here we observed a decline in serum IgA and IgG contents of laying ducks fed diet with organic acid mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were similar to many studies, which also determined that coccidia and C. perfringens challenged significantly increased duodenum and jejunum lesions scores ( Attia et al, 2012 ; Rodrigues et al, 2017 ; Gharib-Naseri et al, 2019 ). Mustafa et al (2021) indicated that the dietary supplementation with organic acids in coccidial challenged group could improve intestinal health, and reduce intestinal lesions scores of broiler chickens. Another study showed that adding 120 mg/kg of essential oils (thymol and carvacrol) after C. perfringes challenged significantly reduced lesions scores in chickens ( Yin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, piglets from the benzoic acid group showed a higher concentration of acetate, propionate, butyrate and all short-chain fatty acids in the ileum or cecum. The mix of organic acid administered to chicks with coccidiosis mitigated pathological lesions in the jejunum, decreased the depth of crypts and increased the villi height/crypt depth ratio (Mustafa et al, 2021). Sodium butyrate administered orally to Cobb broiler chickens that received an intraperitoneal injection of lipopolysaccharide at a dose of 500 μg/kg, inhibited the reduction of the villous height in the duodenum and ileum caused by a stress factor (Xiong et al, 2018).…”
Section: Organic Acidsmentioning
confidence: 99%